PERFORMANCE ANALYSIS OF STARTUP ENTREPRENEURS PROGRAMS - harry yulianto (AkMen JURNAL ILMIAH, 2019)
An aims of this study was analyzed the performance of the Startup Entrepreneurs Program. The design of this study was quantitative by using a descriptive approach. This research data was secondary data obtained from the Deputy for Financing, the Ministry of Cooperatives and Small and Medium Enterprises. Data collection techniques using document studies. The data analysis technique uses quantitative descriptive. The results of this study: an increase in the distribution of aid recipients in the border areas by 91%; the realization of the number of beneficiaries of the Startup Entrepreneurs Program exceeding the target; women who received the Startup Entrepreneurs Program increased by 165% if compared to 2017; the growth in the field of business beneficiaries of the Startup Entrepreneurs Program experienced a significant increase in the culinary business sector; the quantity of labor absorption shows an increase in labor absorption of 101% compared to 2017; and the allocation of assistance for the Startup Entrepreneurs Program has been spread evenly to all provinces in Indonesia. Penelitian ini bertujuan menganalisis kinerja Program Wirausah Pemula. Desain penelitian ini adalah kuantitatif dengan menggunakan pendekatan deskriptif. Data penelitian ini adalah data sekunder yang diperoleh dari Deputi Bidang Pembiayaan, Kementerian Koperasi dan Usaha Kecil dan Menengah. Teknik pengumpulan data menggunakan studi dokumen. Teknik analisis data menggunakan deskriptif kuantitatif. Hasil penelitian ini:adanya peningkatan sebaran wilayah penerima bantuan pada daerah perbatasan sebesar 91%; realisasi jumlah penerima bantuan Program Wirausaha Pemula melebihi target; wanita penerima bantuan Program Wirausaha Pemula mengalami peningkatan sebesar 165% apabila dibandingkan tahun 2017; pertumbuhan bidang usaha penerima bantuan Program Wirausaha Pemula mengalami kenaikan yang signifikan pada bidang usaha kuliner; kuantitas serapan tenaga kerja menunjukkan terdapat kenaikan serapan tenaga kerja sebesar 101% jika dibandingkan tahun 2017; serta alokasi bantuan Program Wirausaha Pemula sudah tersebar secara merata ke seluruh propinsi di Indonesia.